Perceptions of the motivational climate, basic psychological needs, and life skills development in Chinese physical education students - Zheng, Shaofeng; Ji, Xiangbo; Cheng, Liping; Xu, Jianhua; Cronin, Lorcan Donal (Frontiers in Psychology, 2023)
Life skills can have a positive impact on young people’s mental health, academic performance, and overall well-being. Physical education (PE) is viewed as a promising setting for developing students’ life skills, but less is known about this in non-English speaking countries such as China. Based on the integration of Self-Determination Theory (SDT) and Achievement Goal Theory (AGT), we aimed to examine the relationships between students’ perceptions of the teacher-initiated motivational climate (mastery- or performance-oriented) and their life skills development in PE, as well as the mediating role of their basic psychological needs (BPNs) (satisfaction or frustration). We employed a cross-sectional survey. Chinese students (N = 533, Age range = 13-18 years) completed measures assessing these variables. We fulfilled correlational and mediational analyses. These findings showed that mastery climate was positively associated with needs satisfaction (r = .66) and eight life skills (r range = .44 – .61), whereas negatively associated with needs frustration (r = -.49). Performance climate was positively related to needs frustration (r = .52), but negatively related to needs satisfaction (r = -.38) and eight life skills (r range = -.28 – -.15). Needs satisfaction was positively (r range = .44 – .65), whilst needs frustration was negatively (r range = -.50 – -.34) linked with eight life skills. Furthermore, needs satisfaction positively mediated the effect of mastery climate on life skills development, but it is not found that needs frustration mediated the effect of performance climate on life skills besides goal setting, social skills, and time management. In conclusion, our study extended the previous literature on life skills in PE, and highlighted the roles of motivational climate and BPNs on students’ life skills development. In practice, PE teachers should be encouraged to create a mastery climate as well as avoid a performance climate, to foster students’ BPNs satisfaction, which in turn, promote their life skills development.